NOD1 Is Associated With the Susceptibility of Pekin Duck Flock to Duck Hepatitis A Virus Genotype 3 - Liang, Suyun; Wang, Ming-Shan; Zhang, Bo; Feng, Yulong; Tang, Jing; Xie, Ming; Huang, Wei; Zhang, Qi; Zhang, Dabing; Hou, Shuisheng (Frontiers in Immunology, 2021)
Duck viral hepatitis (DVH) is an acute, highly lethal infectious disease of ducklings that causes huge losses in the duck industry. Duck hepatitis A virus genotype 3 (DHAV-3) has been the most prevalent DVH pathogen in the Asian duck industry in recent years. Here, we investigated the genetic basis of the resistance and susceptibility of ducks to DVH by comparing the genomes and transcriptomes of a resistant Pekin duck flock (Z8) and a susceptible Pekin duck flock (SZ7). Our comparative genomic and transcriptomic analyses suggested that NOD1 showed a strong signal of association with DVH susceptibility in ducks. Then, we found that NOD1 showed a significant expression difference between the livers of susceptible and resistant individuals after infection with DHAV-3, with higher expression in the SZ7 flock. Furthermore, suppression and overexpression experiments showed that the number of DHAV-3 genomic copy in primary duck hepatocytes was influenced by the expression level of NOD1. In addition, in situ RNAscope analysis showed that the localization of NOD1 and DHAV-3 in liver cells was consistent. Altogether, our data suggested that NOD1 was likely associated with DHAV susceptibility in ducks, which provides a target for future investigations of the pathogenesis of DVH.